2017
DOI: 10.1039/c7cp02118f
|View full text |Cite
|
Sign up to set email alerts
|

Efficient crystallization-induced emission in fluorenyl-tethered carboranes

Abstract: Fluorenyl-tethered o-carborane derivatives (Fl-Cb) as both mono- and di-aryl Cb assemblies were synthesized from the corresponding alkyne and BH(EtS) in ca. 60% yields. Crystallographic studies of di-aryl examples show rigid head-to-tail or tail-to-tail packing, while for the mono-aryl examples, only loose packing was observed. In solution, the Fl-Cb compounds exhibit strong quenching of their emission, while aggregation in a mixed solvent results in an enhanced, but still weak, emission [0.11 quantum efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…This difference could be the reason of the lower quantum yield in aggregate state in case of 6 comparing with 4 and 5, since the higher density of electronic states in case of 4 and 5 and the significant delocalization of the unoccupied orbitals between the molecules allow relaxation from higher-lying excited states via lower excited states (internal conversion), thus the emission will dominate instead of the non-radiative processes. 94 Thus, the DFT calculations support the idea that the different packing in the crystal structure of 6 causes the lower quantum yield. In contrast to the supramolecular structures of 4 and 5 ( Figure 1), in which each anthracene unit has two neighboring anthracenes from other molecules which are roughly parallel, dimers of 6 are packed twisted.…”
Section: X-ray Diffraction Analysis Of the Crystal Structuressupporting
confidence: 56%
“…This difference could be the reason of the lower quantum yield in aggregate state in case of 6 comparing with 4 and 5, since the higher density of electronic states in case of 4 and 5 and the significant delocalization of the unoccupied orbitals between the molecules allow relaxation from higher-lying excited states via lower excited states (internal conversion), thus the emission will dominate instead of the non-radiative processes. 94 Thus, the DFT calculations support the idea that the different packing in the crystal structure of 6 causes the lower quantum yield. In contrast to the supramolecular structures of 4 and 5 ( Figure 1), in which each anthracene unit has two neighboring anthracenes from other molecules which are roughly parallel, dimers of 6 are packed twisted.…”
Section: X-ray Diffraction Analysis Of the Crystal Structuressupporting
confidence: 56%
“…Even though intense luminescence can be observed in the solution state, optical properties were often spoiled through ACQ by intermolecular interactions in the solid state. [5][6][7] It has been reported that some of the o-carborane [8][9][10][11][12][13] derivatives presented AIE [14][15][16][17][18][19][20][21] and can be applied as a solid-state luminescent material. [1][2][3] Intense solid-state luminescent properties originating from AIE were found and applied for developing the conjugated materials, including polymers.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Additionally, based on environment-responsive intensity changes of the AIE-active materials, various types of film-type luminescent materials and sensors can be fabricated. [5][6][7] It has been reported that some of the o-carborane [8][9][10][11][12][13] derivatives presented AIE [14][15][16][17][18][19][20][21] and can be applied as a solid-state luminescent material. [22][23][24][25][26][27][28][29][30][31][32][33][34] We have also focused on the arylmodified o-carboranes as a scaffold for constructing luminescent "element-block", [35,36] which is defined as a minimum functional unit composed of heteroatoms.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, applicability of the modified o -carboranes for organic light-emitting devices has been demonstrated from the recent studies [ 30 , 31 ]. Moreover, it should be noted that some of the modified o -carboranes also showed AIE [ 23 , 24 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. In the solution state, the modified o -carboranes presented slight emission as a result of emission annihilation by molecular motions, while intense emission was recovered because of low mobility in the solid state.…”
Section: Introductionmentioning
confidence: 99%